Korelasi, Motivasi, dan Prospek terhadap Hasil Belajar Bahasa Indonesia Mahasiswa Amerika di Program BIPA - Mohammad Hudha Nursyairofi; Rizman Usman; Gatut Susanto (Pascasarjana Universitas Negeri Malang, 2020)
Abstract: This research aims to describe the motivation, prospect, and correlation between the two factors in learning Indonesian for American students in BIPA UM. The hypothesis underlying this study is that "there is a positive and significant influence of American students' learning motivations towards their learning outcomes in BIPA UM". This study employs sequential mix methods research design with sequential status or two steps design. The results of this research show that a positive and significant correlation on motivation and students' prospect towards students' learning outcome in BIPA UM. Abstrak: Penelitian ini bertujuan mendeskripsikan wujud motivasi, prospek, dan korelasi mahasiswa Amerika dalam belajar bahasa Indonesia di program BIPA UM. Penelitian ini menggunakan desain sequential mix methods dengan status berurutan atau desain dua tahap. Hasil dari penelitian ini menunjukkan bahwa terdapat korelasi yang positif dan signifikan antara motivasi dan prospek terhadap hasil belajar mahasiswa Amerika di program BIPA UM.